2006
DOI: 10.1017/s0022112006002540
|View full text |Cite
|
Sign up to set email alerts
|

Rotations and cessations of the large-scale circulation in turbulent Rayleigh–Bénard convection

Abstract: We present a broad range of measurements of the angular orientation θ 0 (t) of the largescale circulation (LSC) of turbulent Rayleigh-Bénard convection as a function of time. We used two cylindrical samples of different overall sizes, but each with its diameter nearly equal to its height. The fluid was water with a Prandtl number of 4.38. The time series θ 0 (t) consisted of meanderings similar to a diffusive process, but in addition contained large and irregular spontaneous reorientation events through angles… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
285
3
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(330 citation statements)
references
References 43 publications
39
285
3
3
Order By: Relevance
“…In the spectrum of the angular component, a power-law with an exponent close to -2 is obtained at very low frequencies (VLF). This is analogous to the results of Grandemange et al (2013), and consistent with Brownian dynamics (Brown & Ahlers 2006). Hence the VLF oscillation is a random rotation of the CoP in the azimuthal direction around the axis of the body.…”
Section: On the Symmetry Of The Flowsupporting
confidence: 87%
“…In the spectrum of the angular component, a power-law with an exponent close to -2 is obtained at very low frequencies (VLF). This is analogous to the results of Grandemange et al (2013), and consistent with Brownian dynamics (Brown & Ahlers 2006). Hence the VLF oscillation is a random rotation of the CoP in the azimuthal direction around the axis of the body.…”
Section: On the Symmetry Of The Flowsupporting
confidence: 87%
“…We previously reported the frequency of reorientations (spontaneous changes of the LSC orientation) ω r vs. β, and showed that a Gaussian function fit to ω r (β) with a maximum at some β 0 , which has the same physical meaning as before. We found β 0 = 0.0093 ± 0.0010 rad at R = 9.4 × 10 10 in the large sample [16] and β 0 = 0.0022 ± 0.0006 rad at R = 1.1 × 10 10 in the medium sample [12]. The other parameters measured were the coefficient A representing the potential barrier strength; the LSC temperature amplitude δ; the root-mean-square rotation ratė θ rms ; and the Reynolds number R e .…”
Section: Cancellation Of Preferred Orientation By Tiltmentioning
confidence: 57%
“…Examples of such fits have been shown previously [12,13]. The fit parameter δ is a measure of the amplitude of the LSC and θ 0 is the azimuthal orientation of the plane of the LSC circulation in the sample frame.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations